The Effect of Video Media on Skills Thinking Critically Students of State Senior High School 1 Sragen on Virus Material - Restu Setiaji; Rina Astuti (Biopedagogia, 2023)
Abstract: Critical thinking is an intellectual discipline process to make reasonable decisions in solving problems by considering relative and productive thinking and involves evaluating the supporting evidence and the subsequent conclusions that result. The low critical thinking of class X students of SMA Negeri 1 Sragen is caused because students are still difficult to understand the lessons that have been given by the teacher. The purpose of the study was to determine the effect of video media on critical thinking skills of SMA N 1 Sragen students on viral material. This research is a type of qualitative research with a descriptive approach. The research subjects were 36 students of class X by purposive sampling. Data collection techniques were carried out by means of written tests (essays) and interviews. The data analysis technique is using a post test, which is then combined with data reduction, data presentation, and drawing conclusions. The results of the study indicate that students with high ability categories in general can be said that students can do well on the biology critical thinking test in accordance with the criteria for biological critical thinking in accordance with the indicators of critical thinking questions. Students with moderate abilities have not been able to work on critical thinking test questions. And low-ability students have not been able to work on the critical thinking biology test questions properly in accordance with the criteria for biological critical thinking. Overall, the students of SMA N 1 Sragen have high critical thinking skills.